Plasmids Controlling Synthesis of Hemolysin in Escherichia coli: Molecular Properties - Goebel, Werner (1974)
Covalently closed extrachromosomal deoxyribonucleic acid (DNA) was isolated from alpha-hemolytic wild-type strains of Escherichia coli. Most strains examined were able to transfer the hemolytic property with varying frequencies to nonhemolytic recipient strains. Out of eight naturally isolated alphahemolytic E. coli strains, four contained a set of three different supercoiled DNAs with sedimentation coefficients of 76S (plasmid A), 63S (plasmid B), and 55S (plasmid C). The sedimentation coefficients and the contour lengths of the isolated molecules correspond to molecular weights of 65 × 10(6), 41 × 10(6), and 32 × 10(6). Three alpha-hemolytic wild-type strains carried only one plasmid with a molecular weight of 41 × 10(6), and one strain harbored two plasmids with molecular weights of 41 × 10(6) and 32 × 10(6). Alpha-hemolytic transconjugants were obtained by conjugation of E. coli K-12 with the hemolytic wild-type strains. A detailed examination revealed that plasmids with the same sizes as plasmids B and C of the wild-type strains can be transferred separately or together to the recipients. Both plasmids possess the hemolytic determinant and transfer properties. Plasmid A appears to be, at least in one wild-type strain, an additional transfer factor without a hemolytic determinant. In one case a hemolytic factor was isolated, after conjugation, that is larger in size than plasmid A and appears to be a recombinant of both plasmids B and C.